2020
DOI: 10.31235/osf.io/j4dha
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Privacy Concerns in Chatbot Interactions

Abstract: Chatbots are increasingly used in a commercial context to make product- or service-related recommendations. By doing so, they collect personal information of the user, similar to other online services. While privacy concerns in an online (website-) context are widely studied, research in the context of chatbot-interaction is lacking. This study investigates the extent to which chatbots with human-like cues influence perceptions of anthropomorphism (i.e., attribution of human like characteristics), privacy conc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Moreover, creepiness comes under the emotional aspect related to feelings of threat, uncertainty, or discomfort (Langer & König, 2018), possibly related to the threat of personal data being collected and misused (Jackson, 2018). In studying smart products through a resistance approach, Mani and Chouk (2017) found that privacy concerns influence perceptions of intrusiveness.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…Moreover, creepiness comes under the emotional aspect related to feelings of threat, uncertainty, or discomfort (Langer & König, 2018), possibly related to the threat of personal data being collected and misused (Jackson, 2018). In studying smart products through a resistance approach, Mani and Chouk (2017) found that privacy concerns influence perceptions of intrusiveness.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…Third, AI chatbot design and research are still in their infancy [14]. As technologies advance to highly interactive user interface with realistic digital representations, it is unclear how their connection to certain contextual information, such as a background story, will affect user appeal and engagement [16,[49][50][51]. Such technological advantages tend to serve privileged populations better and can implicitly embody prejudices against those who are vulnerable and marginalized [52].…”
Section: Research Gaps and Questionsmentioning
confidence: 99%
“…This concern, according to another study, can limit consumers' willingness to use a chatbot. 49 Data protectionists criticize the way companies collect and use our data and emphasize that we need to be aware of the data we share. 50 People share a lot of information, such as their location, name and purchasing history, with a chatbot, and, interestingly, they are often unaware of this.…”
Section: Privacy Issuesmentioning
confidence: 99%